Cataract and Risk of Fracture: A Systematic Review, Meta-Analysis, and Bayesian Network Meta-Analysis - Gallo Afflitto, Gabriele; Aiello, Francesco; Surico, Pier Luigi; Malek, Davina A; Mori, Tommaso; Swaminathan, Swarup S; Maurino, Vincenzo; Nucci, Carlo (Ophthalmology (Rochester, Minn.), 2025)
To evaluate the odds ratio (OR) and hazard ratio (HR) of bone fracture in phakic subjects with cataract compared with phakic subjects without cataract and pseudophakic individuals. Despite the growing recognition of the link between cataract and fracture, the available evidence remains inconclusive. The results of this meta-analysis were reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The study protocol was registered on the International Prospective Register of Systematic Reviews (ID: CRD42024587477). Four electronic databases were searched from their inception to May 2024: PubMed, Embase, Web of Science, and Cumulative Index to Nursing and Allied Health Literature (CINAHL). Two reviewers performed title and abstract screening, full-text assessment, and study quality appraisal. Frequentist inference meta-analysis and Bayesian network meta-analyses (NMAs) were conducted to assess the OR and HR of fracture among the 3 groups of interest. Sixteen articles met the predefined inclusion and exclusion criteria, with the 11 included in the quantitative synthesis encompassing a population of 4 713 458 subjects and reporting on 284 811 fractures. The certainty of evidence was rated from low to moderate. Compared with subjects without cataract, the OR and the HR for fractures in the cataract group were 1.44 (95% confidence interval [CI]: 0.75-2.75; P > 0.05) and 1.51 (95% CI: 1.14-2.01; P = 0.0152), respectively. Bayesian NMAs indicated that subjects with cataracts have an increased OR and HR of fractures compared with both phakic subjects without cataracts (OR: 3.0 [95% credible interval [CrI]: 2.8-3.3]; HR 1.1 [95% CrI: 1.09-1.12]) and pseudophakic individuals (OR: 1.7 [95% CrI: 1.6-1.8]; HR: 1.28 [95% CrI: 1.24-1.31]). Pseudophakic individuals exhibit a 27% reduction in fracture risk compared with phakic individuals with cataracts, with 1 less fracture event for every 8 pseudophakic subjects. Low-certainty evidence suggests a higher fracture risk in individuals with cataract compared with those without. Moderate-certainty evidence indicates that pseudophakic individuals have the lowest fracture risk compared with phakic patients with or without cataract. Further research should explore the causal link between cataract and fracture risk and evaluate the impact of cataract surgery on fracture prevention. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.